2003
DOI: 10.1002/jmor.10113
|View full text |Cite
|
Sign up to set email alerts
|

Architectural properties of distal forelimb muscles in horses,Equus caballus

Abstract: Articular injuries in athletic horses are associated with large forces from ground impact and from muscular contraction. To accurately and noninvasively predict muscle and joint contact forces, a detailed model of musculoskeletal geometry and muscle architecture is required. Moreover, muscle architectural data can increase our understanding of the relationship between muscle structure and function in the equine distal forelimb. Muscle architectural data were collected from seven limbs obtained from five thorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 24 publications
5
91
2
Order By: Relevance
“…This relative diminishment in distal limb mass is a steady component of animal adapted for rapid movement (Brown et al, 2003a;Pasi and Carrier, 2003;Payne et al, 2005 a and b) and supports the observation that high-speed animals have lighter distal limbs (Hildebrand and Hurley, 1985;Steudel, 1990).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This relative diminishment in distal limb mass is a steady component of animal adapted for rapid movement (Brown et al, 2003a;Pasi and Carrier, 2003;Payne et al, 2005 a and b) and supports the observation that high-speed animals have lighter distal limbs (Hildebrand and Hurley, 1985;Steudel, 1990).…”
Section: Discussionmentioning
confidence: 61%
“…This highlights the replacement of muscle volume with tendon. This phenomenon has been investigated before in various animals (Pasi and Carrier, 2003;Brown et al, 2003a;Payne et al, 2005a;Smith et al, 2006). This study demonstrated that fiber length and PCSA are considered to be a crucial muscle features.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the fact that muscles have small volume, short fibers and large PCSA shows that they have a high power generation capacity. Consequently, the force required for the muscle to be dynamic or static is produced by the muscles with a small volume and long tendons [7,8,23,24] . In the study, it was observed that the muscles in the distal of front and hind legs of Malakan horses generally had small volume, short fibers and high PCSA.…”
Section: Discussionmentioning
confidence: 99%
“…While the muscle structure may vary between different muscles of the individual [7,8] , the same muscles in different individuals can be different in terms of structure [9,10] . Also it is known that exercise [11] , genetic structure and gender [12] are effective on the characteristics of the muscle structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation